A novel research on the subject of the load-independent microhardness performances of Sr/Ti partial displacement in Bi-2212 ceramics - Ülgen, Asaf Tolga; Zalaoğlu, Yusuf; Turğay, Yusuf; Erdem, Ümit; Türköz, Mustafa Burak; Yıldırım, Gürcan (SPRINGER, 2020)
This work is interested in the critical changes in the load-independent microhardness performance parameters with the partial substitution of Sr2+ inclusions for the Ti4+ impurities in the Bi-2212 inorganic solids with the help of the theoretical approximations as regards Meyer's law (ML), proportional sample resistance (PSR), modified proportional sample resistance (MPSR), elastic/plastic deformation (EPD), Hays-Kendall (HK) and indentation-induced cracking (IIC) models found on the experimental microhardness tests applied to a variety of test loads between 0.245 and 2.940 N for the first time. Moreover, Ti-substituted Bi-2212 bulk ceramics (Bi2.1Sr2.0-xTixCa1.1Cu2.0Oy) are prepared within mole-to-mole ratios of x = 0.000, 0.010, 0.030, 0.050, 0.070, 0.100 by the standard solid-state reaction method in the atmospheric pressure conditions. It is provided that Ti partial substitution in the superconducting system descends unsmilingly the mechanical durability, stability, strength, toughness, critical stress, stiffness and flexural strengths of Bi-2212 superconducting solids studied owing to the increment of crystal structural problems. Moreover, it is obtained that the degradation in the crystal structural leads to diminish the typical ISE characteristic of Bi-2212 superconducting ceramic compounds. At the same time, the results show that all the models (especially IIC approach) can serve as the suitable descriptors for the determination of the variation in the load-independent mechanical performances of the Bi-2212 superconducting materials.